On the line: Women and Fish Plant Jobs in Atlantic Canada - Lamson, Cynthia (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1986)
On the Line : Women and Fish Plant Jobs in Atlantic Canada